Poly (Lactic-Co-Glycolic) Acid-Poly (Vinyl Pyrrolidone) Hybrid Nanoparticles to Improve the Efficiency of Oral Delivery of β-Carotene - Wan-Yi Liu; Yun-Shan Hsieh; Yu-Tse Wu (MDPI AG, 2022)
The aim of this study was to develop a nanoparticle formulation made of poly (vinyl pyrrolidone) (PVP) and poly (lactic-co-glycolic) acid (PLGA) for the oral delivery of β-carotene (BC). The hybrid nanoparticles were prepared by the interfacial deposition method, and the physicochemical properties of this formulation were characterized in terms of its morphology, particle size, size distribution, encapsulation efficiency, dissolution, intestinal permeability, and in vivo pharmacokinetics. Our results demonstrated that BC-loaded nanoformulation and PLGA nanoparticles (PNP) significantly enhanced a release 6.1 times higher than BC suspension. The fortification of PVP into PLGA nanoparticles, named PLGA-PVP hybrid nanoparticles (PPNP), significantly reduced the particle size, as well as led to an increase 1.9 times higher in the in vitro release of BC, compared with PNP. For the ex vivo intestinal permeability assessment, PNP and PPNP-K15 significantly enhanced the intestinal permeability by 2.7 and 6.5 times at the jejunum, and 2.3 and 4.5 times at the ileum, when compared with unformulated BC. According to the pharmacokinetic study, the optimized hybrid formulation significantly increased the peak plasma concentration (Cmax) and the area under the curve (AUC0-t), and the oral relative bioavailability showed a five-fold enhancement compared with that of the BC suspension. Our results indicate that the hybrid nanoparticulate delivery system is an efficient strategy for the oral delivery of BC.